A donor risk index for graft loss in pediatric living donor kidney transplantation - Wasik, Heather (Am J Transplant, 2019)
Pediatric kidney transplant (KT) candidates often have multiple potential living donors (LD); no evidence-based tool exists to compare potential LD, or to decide between marginal LD vs deceased donor (DD) kidney transplantation (KT). We developed a pediatric living kidney donor profile index (P-LKDPI) on the same scale as the DD KDPI by using Cox regression to model the risk of all-cause graft loss as a function of living donor characteristics and DD KDPI. HLA-B mismatch (aHR per mismatch=(1.04)1.27(1.55)), HLA-DR mismatch (aHR per mismatch=(1.02)1.23(1.49)), ABO incompatibility (aHR=(1.20)3.26(8.81)), donor systolic blood pressure (aHR per 10mm Hg=(1.01)1.07(1.18)), and donor eGFR (aHR per 10 ml/min/1.73m(2)=(0.88)0.94(0.99)) were associated with graft loss after LDKT. Median (IQR) P-LKDPI was −25 (−56-12). 68% of donors had P-LKDPI<0 (less risk than any DD kidney) and 25% of donors had P-LKDPI>14 (more risk than median DD kidney among pediatric KT recipients during study period). Strata of LDKT recipients of kidneys with higher P-LKDPI had a higher cumulative incidence of graft loss (39% at 10 years for P-LDKPI≥20, 28% for 20>P-LKDPI≥−20, 23% for −20>P-LKDPI≥−60, 19% for P-LKDPI<−60 (log rank p<0.001)). The P-LKDPI can aid in organ selection for pediatric KT recipients by allowing comparison of potential LD and DD kidneys.